Alterity and the Literature Classroom (Or, I Look for the Other When I Teach) - J. Neil C. Garcia (Humanities Diliman, 2015)
This paper builds on a plenary lecture that the author delivered in 2009, before an audience of college literature teachers in a big private university in Manila. The theme of the conference was the teaching of literature, and in his presentation he argues that the “otherness” of Philippine literature in English requires a deconstructive reading/teaching strategy that will move away from the universalist interpretation of its themes in order to pursue a specifying postcolonial analysis of its political “unconscious” (which references, by definition, the history of neo/colonial relations that, to begin with, made this tradition of writing possible). To the author, Levinasian alterity denominates a philosophical understanding that may alert the postcolonial literature teacher to the importance of carrying out such an interpretive project, because what it prompts and urges, in the end, is both a recognition of and a respect for the “absolutely other,” the responsible relationship with whom is the very ground of subjectivity itself. Finally, the author offers a postcolonial reading of Paz Marquez Benitez’s “Dead Stars” in order to illustrate the generativity of this approach, in the process laying bare the critical difference that conventional humanist readings of this famous and inaugural text are unable—or simply refuse—to acknowledge.